Strokes among black people in Harare, Zimbabwe: results of computed tomography and associated risk factors. Issue 6536 (21st June 1986) - Matenga, J; Kitai, I; Levy, L
Abstract : Computed tomography was performed and risk factors evaluated in 100 consecutive adult patients presenting to the two teaching hospitals in Harare with a clinical diagnosis of stroke. The mean age of the patients was 52; only 28 were 65 or older. Non-stroke lesions were found in seven patients and were predicted by a recent history of convulsions (p less than 0.0001). Five lesions (four subdural haematomas and one cerebral cysticercosis) were remediable. Hypertension was present in 27 (93%) of the 29 patients with cerebral haemorrhage and in 49 (53%) of the 93 patients with stroke lesions. In 22 (45%) of these patients the hypertension had not been diagnosed, and another 22 had defaulted from treatment. All 13 patients who died before computed tomography had hypertension, and over half showed evidence of haemorrhagic stroke. There was a cardiac source for all 12 cases of cerebral embolism. In eight of the 100 patients cerebral infarction was attributed to neurosyphilis. None of the patients had clinical evidence of atherosclerosis. Smoking and oral contraceptives did not seem important risk factors for stroke. Detection and control of hypertension remain the most important measures needed to reduce the incidence of and mortality from stroke in Zimbabwe.